Risāla-yi jild sāzī : Ṭayyāri-yi jild - Ḥusayn, Sayyid Yūsuf, (Miras Maktoob, ISBN: 9789004365452., 2019)
Before the printing press made its appearance in the Islamic world, books were reproduced in manuscript, as was the case in Europe before Gutenberg (d. 1468) introduced printing in movable type. In that connection, the art of bookbinding was very important. This may be inferred from a special chapter devoted to this subject in Ibn Bādīs' (d. 453/1061) ʿ Umdat al-kuttāb wa-ʿuddat dhawi ʼl-albāb , or from Ibn Abī Ḥamīda's (9th/15th century) didactic poem for bookbinders, called Tadbīr al-safīr fī ṣināʿat al-tasfīr . The present work is a new and improved edition of a didactic poem on bookbinding in Persian, composed in India by a certain Sayyid Yūsuf Ḥusayn, somewhere before 1228/1813. About the author not much is known other than that his knowledge of Persian shows some shortcomings and that he must have had mystical leanings. This new edition follows the discovery of another copy of this text in Iran, besides the one kept in Madras (Chennai)